The Setiu Wetland's loss of attractiveness to tourist destination facilities: eco-touristic educational experiences / Balqis Aminuddin ... [et al.] - Aminuddin, Balqis; May Ling, Siow; Herman, Siti Sarah; Ismail, Sumarni (2022)
Setiu Wetland, Terengganu, Malaysia, has vast eco-tourism potential. An eco-touristic educational experience provided by tourism facilities is an important strategy for reducing negative impacts on the environment. However, growth has been limited by the loss of appeal of coastal wetland tourist destinations, because of the lack of innovative and up-to-date tourism facilities. The lack of physical development of wetland facilities has contributed to a drop in the number of tourists visiting the wetland, an issue aggravated by a lack of defined policies or norms regulating these facilities at the National level. In Setiu Wetland, deficiencies in physical design facilities for eco-touristic educational experiences must be identified. This study investigated the gaps in physical facilities designed for eco-touristic educational experiences in Setiu Wetland. Three methods will be used in this study: planning documents, virtual and on-site observation, as well as an in-depth interview. The information was much more precise after an in-depth interview with the caretaker and a stakeholder. There is a need to formulate appropriate design strategies to support the main stakeholder's involvement in the investigation of eco-touristic education on existing coastal wetland facilities.